2022
DOI: 10.1021/jacs.2c05565
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Radical SAM Oxygenase for the Ether Crosslinking in Darobactin Biosynthesis

Abstract: Darobactin A is a ribosomally synthesized, post-translationally modified peptide (RiPP) with potent and broad-spectrum anti-Gram-negative antibiotic activity. The structure of darobactin A is characterized by an ether and C–C crosslinking. However, the specific mechanism of the crosslink formation, especially the ether crosslink, remains elusive. Here, using in vitro enzyme assays, we demonstrate that both crosslinks are formed by the DarE radical S-adenosylmethionine (SAM) enzyme in an O2-dependent manner. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
61
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(66 citation statements)
references
References 29 publications
5
61
0
Order By: Relevance
“…To obtain sufficient amount of 1 for further structural characterization, we tried on different commercially available proteases and found that proteinase K can efficiently release 1 from modified PasA in vitro (Figure S11), in a way similar to the recent work on darobactin . We scaled up the expression, digestion, and purification process, which afforded 1.5 mg of 1 for NMR characterization.…”
Section: Results and Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…To obtain sufficient amount of 1 for further structural characterization, we tried on different commercially available proteases and found that proteinase K can efficiently release 1 from modified PasA in vitro (Figure S11), in a way similar to the recent work on darobactin . We scaled up the expression, digestion, and purification process, which afforded 1.5 mg of 1 for NMR characterization.…”
Section: Results and Discussionmentioning
confidence: 97%
“…(A) Maximum likelihood phylogenetic tree of the daropeptide precursors. The daropeptide precursors investigated in previous studies (i.e., pk -DarA, , pl -DarA, and yi -DarA) and in this study (i.e., PasA and RscA) are marked by white circle and yellow circle, respectively. Key bootstrap values for tree construction are indicated along the branch.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…OxsB then catalyzes dehydrogenation of the C2′-CH 3 methyl to yield the methylidene 10-P rather than a second round of methylation as observed in other radical-mediated methyltransferases. Although examples of radical SAM catalyzed dehydrogenation of alcohols, thiols, and amines are well-known, biological C-CH 3 dehydrogenase activity has not been previously reported for a radical SAM enzyme. Nevertheless, NosL from nosiheptide biosynthesis catalyzes C–C desaturation of a substrate structural analogue, and DarE from the darobactin maturation pathway has been identified to catalyze off-pathway dehydrogenation of the C α –C β bond of a tryptophan residue in its peptide substrate. , Once formed, 10-P could then serve as an acceptor for OxsB catalyzed addition of the 5′-deoxyadenosyl radical ( 2 ). This chemistry is effectively equivalent to that of MqnE and QueE requiring ejection of one electron from the reduced radical adduct such that the overall addition (i.e., 10-P + SAM → 11-P + Met) is redox neutral .…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, NosL from nosiheptide biosynthesis catalyzes C−C desaturation of a substrate structural analogue, 39 and DarE from the darobactin maturation pathway has been identified to catalyze off-pathway dehydrogenation of the C α −C β bond of a tryptophan residue in its peptide substrate. 40,41 Once formed, 10-P could then serve as an acceptor for OxsB catalyzed addition of the 5′deoxyadenosyl radical (2). This chemistry is effectively equivalent to that of MqnE 42 and QueE 43 requiring ejection of one electron from the reduced radical adduct such that the overall addition (i.e., 10-P + SAM → 11-P + Met) is redox neutral.…”
Section: ■ Introductionmentioning
confidence: 99%